PENGARUH RETURN ON ASSETS, RETURN ON EQUITY DAN NET INTEREST MARGIN TERHADAP RETURN SAHAM BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2015-2019. - Aam Abdul Salam (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2020)
ABSTRACT: From this research aims to find out return on assets, return on equity and net interest margin that affect simultaneously or in part against the share price on the Indonesia Stock Exchange. This research is a comparative causal data source used from bank aunual reports 2015 to 2019 from the Indonesia Stock Exchange. According to the criteria in this study, the sample is 4 i.e. state-owned banks. To analyze models and test research hypotheses, we used several statistical methods of linear regression analysis. Based on the results of hypothetical research and tests, we can conclude as follows: 1) ROA, ROE and NIM have a significant effect on stock returns. 2) ROA and ROE ratios, partially affecting stock returns, while NIM ratios have been shown to have no affect. Keywords : Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), return shares.